Law Due To The Transfer Of Land Under Hand With Deed As Evidence (Case Study In Kendari) - Steffi Yesyer Palloan; Akhmad Khisni (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2020)
The purpose of this study as follows 1) To identify and explain the legal effect on the transition of land right under the deed of hand as evidence. 2) To identify and explain the weaknesses of the transitional land right under the deed of hand. 3) To identify and explain the transfer of land rights solutions with deed under the hand. The method used by researchers is approach to law juridical sociological and specification in this study were included descriptive analysis. The sources and types of data in this study are primary data obtained from field studies with interviews with the Notary in Kendari. And secondary data obtained from the study of literature. Based on the results of research The absence of legal certainty for those who receive the new rights over the land in question, as for a way to resolve that can be achieved is by registering the transfer of land rights to the Land Office. Many people who do not register the transfer of rights or title transfer to the Land Office is the lack of information about the process of the registration of the land, there are many people who make the switch right to the land under the hand not in front of PPAT, economic factors, the cost of registration of transfer of rights is fairly high and not transparent and there are still many who do not own land Earth Building Tax. Direct settlement by parties with deliberation. Through arbitration and alternative dispute resolution. Judicial dispute resolutionKeywords: Transfer of Rights to Land; Under Hands Deed; Evidence.